2013
DOI: 10.4103/1319-2442.118099
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic urolithiasis in Tunisian children: A report of 134 cases

Abstract: We evaluated the metabolic and the nutritional aspects of 134 urolithiasis children in order to outline the characteristics of idiopathic urolithiasis in children. This prospective study group of 134 children (56 females, 78 males) with renal calculi was evaluated. The age range of the patients was six months to 16 years. A dietary survey was performed on every child. All patients were investigated with respect to stone localization and serum and urine risk factors. Statistical analysis of data was carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 0 publications
0
8
0
3
Order By: Relevance
“…The changes in dietary habits and consumption of oxalate-rich foods among the pre-school children seem to be an important cause of hyperoxaluria in these children; studies have shown that hyperoxaluria is significantly higher when the children are >1 year and are switched to solid foods [12,14]. The hot climate and higher prevalence of consanguineous marriage are other causes of hyperoxaluria in our region [17,19]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The changes in dietary habits and consumption of oxalate-rich foods among the pre-school children seem to be an important cause of hyperoxaluria in these children; studies have shown that hyperoxaluria is significantly higher when the children are >1 year and are switched to solid foods [12,14]. The hot climate and higher prevalence of consanguineous marriage are other causes of hyperoxaluria in our region [17,19]. …”
Section: Discussionmentioning
confidence: 99%
“…This may be one of the reasons for the recent increase in the incidence of urolithiasis in children, due to the important inhibitory effect of citrate on stone formation [23]. It is believed that dietary habits in older children, mainly diets containing high sodium and animal protein with low fruit and vegetables and environmental factors such as soil properties, play a key role in the lower citrate excretion in the urine [14,19,23,24]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported that the annual incidence of pediatric urolithiasis has increased over the last century in response to the risk factors including dietary changes, metabolic abnormalities, climate change, infection patterns, and genitourinary abnormalities. [4][5][6][7][8][9] In Tunisia, the dietary habit such as an increase in animal protein intake and increased intake of starchy foods and food with high oxalate content influenced the stone formation in children. 4 In the USA, the sex distribution of pediatric urolithiasis varied with age, and there is a possibility of the hormonal effect on the stone formation.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9] In Tunisia, the dietary habit such as an increase in animal protein intake and increased intake of starchy foods and food with high oxalate content influenced the stone formation in children. 4 In the USA, the sex distribution of pediatric urolithiasis varied with age, and there is a possibility of the hormonal effect on the stone formation. 5 In Thailand, the high prevalence of metabolic disorders such as renal tubular acidosis was associated with the high prevalence of renal stone associated with hypocitraturia.…”
Section: Introductionmentioning
confidence: 99%